Peran Psikologi Manajemen dalam Pendidikan dan Organisasi: Kajian Sistematis terhadap Efektivitas dan Adaptasi Kinerja - Yusnida Abila; Wardatul Kamilah; Hulwatun Nisa’; Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Management psychology is an essential element in addressing the dynamics of modern organizational change, particularly in efforts to improve performance effectiveness, educational quality, and human resource development. The complexity of individual behavior within organizations requires psychological approaches that are integrated with management practices to optimize human resource management. This study aims to examine recent developments in management psychology and analyze its contribution to improving organizational quality and effectiveness. The research employed a literature review method by analyzing scientific articles published between 2022 and 2025. Articles were collected from various academic databases and selected based on their relevance and publication quality. The findings reveal three major trends in management psychology: the implementation of emotional intelligence-based leadership, the enhancement of employee psychological well-being, and the utilization of digital technology in human resource management. These aspects have been shown to contribute significantly to increased productivity, work motivation, employee engagement, and organizational adaptability in responding to environmental changes. Therefore, management psychology plays a strategic role in creating organizations that are more effective, adaptive, and sustainable amid continuously evolving global challenges.